การใช้คำอ้างอิง: กรณีการใช้คำบรรยายสีที่เกินความจำเป็น - Arden, Jeeranan (วารสารภาษาปริทัศน์, 2022)
Prior investigations (e.g., Davis & Katsos, 2009; Engelhardt et al., 2006; Rubio-Fernández, 2016) suggest that native speakers of English tend to be overspecified in their referring expressions by including unnecessary adjectival modifiers that do not serve to differentiate the intended referent from other objects in the context, and the most redundantly provided modifiers have been found to be color terms. The phenomenon is known as color overspecification, and contradicts the Maxim of Quantity (Grice, 1975), which states that speakers are expected to provide sufficient information but no more than is necessary for their interlocutors. This study was conducted on Thai EFL speakers to examine whether the phenomenon also occurs in EFL settings. The study examined the participants on their referring expressions in which objects in comparison were in monochrome and in polychrome. The experimental items were adapted from the study of Rubio-Fernández in 2016 as they could yield findings concerning the phenomenon. The findings revealed that the majority of participants produced overspecified referring expressions concerning color terms in the two experimental conditions. They, however, did it significantly more often when objects in the context were in polychrome. This suggested that shades of color play a role in reference production as well. The findings also revealed underlying factors that could influence the participants’ referring expressions. Overall, what is noteworthy is that the results of the study have proven that color overspecification occurs not only to native speakers but also to EFL speakers.